Extreme modules over the Weyl algebra A_n - Bavula, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Certain classes of simple modules over generalized Weyl algebras (extreme modules, polynomial modules, and modules with strong D-torsion) are classified. For these algebras, analogs of the Bernshtein and Stafford theorems are proved.